THE INFLUENCE OF FINANCIAL RATIO ANALYSIS ON FIRM VALUE WITH FINANCIAL DISTRESS AS INTERVENING VARIABLE IN MANUFACTURE COMPANIES LISTED IN IDX - Trito, Belthasar Siahaan (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the effect of financial ratio on firm value with financial distress as an intervening variable on manufacture companies listed in IDX period 2013-2015. This type of research is causal comparative. Sampling method was using proportional random sampling, the company obtained by sample were 59 companies out of 144 companies with a total population of 177 observation units of analysis. Data collection was using data documentation technique from the annual financial statement published by the website www.idx.co.id. The methods of data analysis were using classic assumption test, multiple linear regression analysis test and mediation test with Path Analysis using Sobel test. The results of this research showed that liquidity, solvability, profitability and financial distress simultaneously and partially had significant effect on firm value manufacture companies listed in IDX. The result of indirrectly test showed that variable liquidity solvability and profitability had no significant effect on firm value through financial distress as an intervening variable and financial distress not proven as an intervening variable.